Effect of heart rate on B-type natriuretic peptide in sinus rhythm - Keisuke Fukushima; Kazuo Ogawa; Makoto Kawai; Michihiro Yoshimura (Scientific Reports)
Abstract B-type natriuretic peptide (BNP) levels accurately reflect the degree of cardiac overload in heart failure. Considering cardiac morphology and intracardiac pressure, including the left ventricular end-systolic volume index (LVESVI) and left ventricular end-diastolic volume index (LVEDVI), is essential for cardiac overload assessment. These indexes influence plasma BNP levels, and high heart rate is likely associated with cardiac morphology. However, the direct relationship between high heart rate and plasma BNP levels remains unknown. In this study, we simultaneously measured various hemodynamic parameters and plasma BNP levels during cardiac catheterization in 5,429 inpatients with sinus rhythm at our hospital. Furthermore, we examined how heart rate is associated with cardiac morphology, intracardiac pressure, and plasma BNP levels via regression analysis and structure equation modeling (SEM). Univariate regression analysis revealed a significant positive correlation between heart rate and log BNP. The path model with SEM revealed significant positive relations of heart rate and LVESVI with left ventricular end-diastolic pressure, in addition to a significant negative relation of heart rate and LVEDVI with log BNP. Collectively, these findings suggest no positive relation (rather, a negative relation) between heart rate and log BNP and that high heart rate is indirectly associated with increased plasma BNP levels by altering cardiac morphology and intracardiac pressure.